INSURANCE COMPANY PERFORMANCE ANALYSIS BEFORE AND DURING THE COVID-19 PANDEMIC (STUDY OF GENERAL INSURANCE COMPANIES LISTED ON THE IDX IN 2018-2022) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The Covid-19 pandemic has slowed Indonesia's economic growth. The insurance sector directly affected by the Covid-19 pandemic. In the insurance industry, policyholders tend to decline due to economic pressure on people's purchasing power which causes premiums to rise, but claims actually increase during the Covid-19 pandemic. To see the financial performance of the insurance industry before and during the pandemic, the authors conducted an analysis of the performance of insurance companies which can be reflected in an early warning system which consists of several ratios, including cost loss ratio, equity ratio and overgrowth ratio. The purpose of this research is to find out how these three ratios affect the solvency of insurance companies before and during the Covid-19 pandemic. The solvency level of an insurance company is represented by Risk Based Capital (RBC). The base set used in this study is insurance companies registered in Indonesia for 2018-2022. As a research hypothesis, panel data analysis was tested using the Eviews program. The results of this study indicate that the Claim Expense Ratio, the Premium Growth Ratio and the Self-Retention Ratio affects the Solvency Level during the Covid-19 pandemic.
Keywords: Covid-19; Company Performance Analysis; Early Warning System; Insurance Industry